2014
DOI: 10.7567/jjap.53.05fk01
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved photoluminescence spectroscopy of Ce:Gd3Al2Ga3O12 crystals

Abstract: Time-resolved photoluminescence (PL) spectra of Ce-doped Gd3Al2Ga3O12 (Ce:GAGG) crystal have been measured at various temperatures under Ce3+ 4f → 5d excitation. All time-resolved PL spectra show only a Ce3+ 5d → 4f band around 2.3 eV. Decay curves of this band consist of a fast and slow components. The temperature dependence of integrated intensities of the fast and slow components are analyzed by considering nonradiative processes starting from the ground level of an electron trap. From the results of analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Optical properties of Ce:GAGG crystals have been reported so far [8][9][10]. A typical emission spectrum exhibits a broad band around 2.3 eV, which arises from the Ce 3+ 5d-4f transition.…”
Section: Introductionmentioning
confidence: 97%
“…Optical properties of Ce:GAGG crystals have been reported so far [8][9][10]. A typical emission spectrum exhibits a broad band around 2.3 eV, which arises from the Ce 3+ 5d-4f transition.…”
Section: Introductionmentioning
confidence: 97%
“…As a representative, Ce 3+ -doped multiple aluminate garnet compounds, (Ce,Gd) 3 (Al,Ga) 5 O 12 (Ce:GGAG), have been proposed to be one of the promising scintillators for applications of X-ray detection, medical imaging etc. [11][12][13][14][15] The emission of Ce 3+ in it is characterized by an electron transition from the lowest 5d (5d 1 ) energy level to the 4f energy level 16,17 which could realize both fast decay time and high LY.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Ce:GAGG phosphorescence [4][5][6][7][8][9][10][11][12] have indicated that it is mainly attributed to the formation of shallow electron traps. It was recently demonstrated that these traps are defect complexes of antisite Gd 2+ ions adjoining O vacancies, 13) and first-principles calculations have revealed that they are formed in Al/Ga-deficient compositions.…”
mentioning
confidence: 99%